Upaya Meningkatkan Motivasi Belajar PPKN dengan Model Pembelajaran Problem Based Learning Setelah Covid-19 di SMPN 2 Siak-Riau - Erlisda Wahyuni; Supentri (CV Insan Kreasi Media, 2022)
Indonesia is one of the countries that has been exposed to the Covid-19 outbreak since March 2020 until now which has an impact on education in Indonesia. The policy taken by the government in carrying out the teaching and learning process so that it continues to take place online is one of the policies that causes a decrease in student learning motivation, especially for Civics subjects, where previously education in Indonesia was always carried out face-to-face, after the Covid-19 case declined. each school conducts face-to-face activities on a limited basis. This research was conducted as an effort to increase students' motivation to learn Civics by using the Problem Based Learning learning model after the Covid-19 case in class VIII 3 of SMPN 2 SIAK. Data collection techniques were taken by filling out questionnaires and observation sheets. The data obtained in this study is quantitative data and uses descriptive data analysis with a percentage where each cycle is always repaired or reflected. The results of the study with an average student learning motivation in the pre-cycle of 75.84%, in the first cycle of 78.18%, and in the second cycle of 84.93%, it can be concluded that the use of Problem Based Learning learning models can increase learning motivation student.